Determining Trending Topics in Twitter with a Data-Streaming Method in R - Mediayani, Melani; Wibisono, Yudi; Riza, Lala Septem; PÃ©rez, Alejandro Rosales (Universitas Pendidikan Indonesia, 2019)
Trending topics in Twitter is a collection of certain topics that are widely discussed by users. This study aims to design a model and strategy for finding trending topics from data streams on Twitter. The research approach was carried out in four stages, namely twitter data collection, preprocessing data, data analysis with sequential K-Means clustering and information processing. Sequential K-Means is used because it can receive input data sequentially and the cluster center can be updated. Testing of the model is carried out in three scenarios where each scenario is distinguished between the amount of data, time and parameter values. After that, evaluation of the results of clustering will be done using the Dunn Index method. Trending topics twitter application were created using the R language and produce output in the form of histograms. There are five topics being the trending topics in New York before the new year. The topic of